2018
DOI: 10.1080/10245332.2017.1422315
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity analysis of variations and prenatal diagnosis in a hereditary coagulation factor XIII deficiency family

Abstract: We first established the PND procedure with pathogenicity assessment in FXIIID patients. The F13A gene mutations' spectrum of the Chinese Han population was enriched.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The FXIII level of this patient was less than 5% after which the parents terminated the pregnancy [30]. Previous studies have reported PND for FXIII deficiency, using invasive methods, such as amniocentesis and CVS [31,32]. The only report of PND for FXIII deficiency in Iran was published by Naderi et al in 2016 using CVS samples from eight fetuses.…”
Section: Discussionmentioning
confidence: 76%
“…The FXIII level of this patient was less than 5% after which the parents terminated the pregnancy [30]. Previous studies have reported PND for FXIII deficiency, using invasive methods, such as amniocentesis and CVS [31,32]. The only report of PND for FXIII deficiency in Iran was published by Naderi et al in 2016 using CVS samples from eight fetuses.…”
Section: Discussionmentioning
confidence: 76%
“…That subject's FXIII level was shown to be below 5%; consequently the parents terminated the pregnancy (30). PND for FXIIID, using invasive methods such as amniocentesis and CVS, has been reported in previous studies (31,32). The only report of PND for FXIIID in Iran was published by Naderi et al in 2016 on the CVS samples of 8 fetuses.…”
Section: Discussionmentioning
confidence: 94%
“…It is the first cause of death in these patients. Finally, the study's laboratory results a significant relationship between the increase in MMP-9 gene expression and the pathogenesis of intracranial bleeding (18). In the central nervous system, it has been shown that matrix metalloproteinases 9 and 2 (gelatinases) cause the breakdown of basal lamina components, secondarily leading to the destruction of the blood-brain barrier (19).…”
Section: Discussionmentioning
confidence: 94%